Negotiating Cultural Identities in Diaspora: A Conceptual Review of Third Space - Bhandari, Nagendra (Curriculum Development Journal, 2020)
In association with different disciplines, the conceptualization of the third space with different jargons and theoretical tropes has evolved historically. However, this article makes a brief review about the concept of the third space in relation with formation of human subjectivities. Particularly, the ideas of Arnold Van Gennep, Victor Turner, Edward Burghardt DuBois, Gloria Anzaldua and Homi Bhabha are reviewed briefly. In fact, observing the cultural rituals and how they transform human subjectivities, Gennep locates the transitory space which is crucial informing changing roles and identities of human beings. From cultural rituals, Turner takes up this idea in the process of social changes. He identifies this space in between the interaction of structured and anti structured social roles. Likewise, DuBois expands this idea in examining subjectivities of Black people. But, Anzaldua incorporates all people and formation of their identities in her analysis. Multiple factors and allegiances are responsible in forming human identities in her concept. Similarly, Bhabha concentrates in colonial and post colonial context and analyzes how the cultural interactions of colonized and colonizer deconstruct the bipolar concept of cultural identities and give birth of a new form of identities in the hybrid space of cultural interaction. Bhabha’s conceptualization is relevant in conceptualizing immigrants’ cultural identities in diaspora.